Outcomes and Treatment Complications of Intravenous Urokinase Thrombolysis in Acute Ischemic Stroke in China - Zhang, Rongrong; Wei, Hui; Ren, Yu; Wu, Yanping; Luo, Yetao; Zhang, Lei; Huo, Yingchao; Feng, Jinzhou; Monnier, Philippe P.; Qin, Xinyue (Frontiers in Neurology, 2021)
Background Intravenous thrombolysis with alteplase benefits eligible patients with acute ischemic stroke. However, for low-income patients and those from regions with low economic development, alteplase is too expensive. Urokinase is much less expensive than alteplase. This study aimed to assess the outcomes and treatment complications of urokinase in acute ischemic stroke patients, which are poorly understood. Methods This multicenter retrospective study included acute ischemic stroke patients who received intravenous urokinase or alteplase from January 2014 to January 2018 at 21 centers in China. Outcomes and treatment complications were analyzed by univariate and multivariate analyses. Results Among the 618 patients included in this study, 489 were treated with urokinase and 129 were treated with alteplase. Functional independence, no/minimal disability, mortality, intracranial hemorrhage (ICH), and symptomatic ICH did not significantly differ between the urokinase and alteplase groups in the univariate and multivariate analyses. However, the patients who received alteplase had a lower odds ratio (OR) of extracranial bleeding in the univariate analysis and a lower adjusted OR (aOR) in the multivariate analysis than the patients who received urokinase (OR = 0.410 [95% CI, 0.172-0.977], p = 0.038; aOR = 0.350 [95% CI, 0.144-0.854], p = 0.021). Furthermore, in patients treated with urokinase, the patients who received high-dose urokinase had a higher OR of extracranial bleeding in the univariate analysis and a higher aOR of extracranial bleeding in the multivariate analysis than patients who received low-dose urokinase (OR = 3.046 [95% CI, 1.696-5.470], p < 0.001; aOR = 3.074 [95% CI, 1.627-5.807], p = 0.001). Moreover, patients who received low-dose urokinase had similar outcomes and complications compared to patients treated with alteplase. Conclusions Patients treated with urokinase had similar outcomes but a higher risk of extracranial bleeding compared to patients treated with alteplase. The risk of extracranial bleeding was higher in the patients treated with high-dose urokinase than in the patients treated with low-dose urokinase. Patients who received low-dose urokinase had similar outcomes and complications compared to patients treated with alteplase. For acute ischemic stroke patients who cannot afford alteplase, urokinase may be a good choice for intravenous thrombolysis.